An examination of digital news reporting on professional journalism practice : a study of fake sport news and websites - Singh, Kimara (My University, 2020)
This study examined the effect of digital news reporting on professional journalistic practice focusing on fake sport news websites. It evolves from the fact that, despite the progressive benefits of the digital revolution, the rise of fake news websites has become common practice associated with the clickbait that spreads rumours posted on unofficial accounts often with a journalistic pretext. The aim of this study was to examine how fake digital sport news reporting impacts on professional journalistic practice. The objectives of the study were: to describe the nature of internet-based fake sport news stories and websites; to assess the credibility of sport news disseminated through fake news sites, and to determine the implications of fake sport news stories and websites on standard news practice. The descriptive design within the qualitative interpretive paradigm was used to determine the negative effect that fake sport news has on professional journalistic practice. Qualitative content analysis of ten sample news excerpts and in-depth interviews with sixteen expert informants were complementarily used to collect data. Interpretive phenomenological analysis was applied to generate discursive themes which yielded the study outcomes. The data from screenshots and interviews were collected, corroborated and analysed, using content and thematic analysis techniques. After analysing both the screenshots and the interviews, a total of eight themes emerged from the study. The study notes how fake sport news and its associated litany of misinformation and/or disinformation has contributed to the creation of false hypes about sports news to the detriment of professional journalism practice. The study revealed that fake sport news is prominent on social media and poses a major challenge to journalistic integrity and credibility. From the various screenshots, fake headlines were identified as a contributing factor to the rise of fake news stories. It was also found that fake sport news has a negative effect on journalism practice, as it spreads lies, makes people more interested in emotional stories and forces credible news agencies to also use sensational headlines to gain the attention of an audience. The interviews revealed that characteristics of fake sport news stories are exaggerated, misleading, have no source or attributions, no by-lines or unknown authors and misrepresent so-called facts. iv vi The study recommends that research, fact-checking, naming and shaming people/websites that popularize fake sport news should be made known to the public; proper training and assertion of certain rules, regulations and ethics for new reporters and journalists to follow and stick to; there must be thorough research and cross checking of information gained from a secondary source; a governing body to possibly monitor and crack down on serial propagators and spreaders of fake sports news stories; sport journalists should alert readers of fake sport news and fake sport news websites, as these are common in sport due to the popularity of sport news sites; and sport journalists should stay away from reporting/re-writing and sharing fake news in order to maintain credibility and ethics in sport news reporting.
Thesis (M.A. (Media Studies)) -- University of Limpopo, 2020
Keywords: Digital news reporting; Professional journalistic practice; Fake sport news websites; Fake digital sport news reporting; Sport journalists; Journalistic ethics; Journalism; Fake news; News Web sites; Sports journalism